Remote wireless control of aerodrome lighting signal equipment - Ильницкий JI. Я.; Девяткина, С. С. (Proceedings of National Aviation University (archive), 2000)
Considered is the possibility of radiotechnical control of aerodrome lighting signal system in the process of maintenance and repair. Proposed is general approach to construction of the system which is illustrated by the structural and functional scheme. Presented are the reasons of construction of radiotechnical control of aerodrome lighting signal equipment, also proposed are the ways of its realization